2013
DOI: 10.1039/c3ra41450g
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption properties of benzene and water vapor on hyper-cross-linked polymers

Abstract: A series of hyper-cross-linked polymers (HCPs) was synthesized via a post-cross-linking reaction using lowcross-linked polydivinylbenzene (PDVB) as precursor and 4,4 0 -bis(chloromethyl)biphenyl (BCMBP) as crosslinking reagent. The effects of various amounts of BCMBP on the structures of the hyper-cross-linked polymers were discussed. The resultant typical HCP-1.3 possesses hierarchical micro/meso pore structures and a high stability up to 400 C. The increased specific surface area and total pore volume of HCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…1. It is observed that all the samples show a type I isotherm according to IUPAC classifications and the initial parts of the adsorption isotherms of all samples show a steep increase in nitrogen gas uptake (p/p 0 < 0.01), indicating abundant microporous structure [22,26]. Compared with other samples, the adsorption isotherms of HCP-0.5 exhibit a remarkable rise and the desorption branch of the hysteresis loop is steeper than the adsorption branch at higher relative pressure (p/p 0 = 0.3-1.0), indicating that a range of larger mesopores are presented in this polymeric material [27].…”
Section: Characterization Of Hcp-xmentioning
confidence: 99%
See 3 more Smart Citations
“…1. It is observed that all the samples show a type I isotherm according to IUPAC classifications and the initial parts of the adsorption isotherms of all samples show a steep increase in nitrogen gas uptake (p/p 0 < 0.01), indicating abundant microporous structure [22,26]. Compared with other samples, the adsorption isotherms of HCP-0.5 exhibit a remarkable rise and the desorption branch of the hysteresis loop is steeper than the adsorption branch at higher relative pressure (p/p 0 = 0.3-1.0), indicating that a range of larger mesopores are presented in this polymeric material [27].…”
Section: Characterization Of Hcp-xmentioning
confidence: 99%
“…The synthesized HCP-1.3 has high surface area, large pore volume and showed a good adsorption for benzene under water condition due to its high hydrophobic property. However, in our previous paper [22], we only studied the effect of the dynamic adsorption of benzene vapor containing 30% water vapor, and did not investigate the dynamic adsorption behavior of benzene on HCP-1.3 under higher humid conditions. In the latest work [23], we synthesized a conjugated polymer adsorbent with pure carbon chain backbone, which had excellent hydrophobicity and higher adsorption capacity of benzene than activated carbon.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These HPP and HPC materials could hold considerable promise in applications as advanced adsorbents, catalyst supports, energy-storage materials and others. [13,14] 、药物控释 [15,16] 、催化 [17,18] 、能源 [19,20] 以及 环境保护 [21,22] 等领域具有广泛的应用前景. [23,24] .…”
mentioning
confidence: 99%